Study Of Green Movement In Indian Corporate Houses For Sustainable Growth - Kaur, Harpinder (Gyan Management Journal, 2020)
The  Green  Management  is the  requirement  of  21stcentury  because  of  over  consumption  of  non renewable resources as raw material by the organizations.  Industrialization and urbanization has  put tremendous  pressure  on  non-renewable  resources  alarming the  ecological  and  environment  imbalances  in  the  world  .Green  management  is  the  organization-wide  process  of  creating  and  implementing  innovative  techniques  and  initiatives  to  achieve  long  run  sustainability,  social  responsibility, waste reduction and to build competitive advantage on the basis of green products,  services .It also include integrating environmental  sustainable goals and strategies withobjectives of  organization .This research paper tries to explore the ways how Indian Corporate organisations of  modern times are taking initiatives to become green organizations.Setting green goals and actions  make a responsible ,good business sense  .Data hasbeen collected  for Twenty four Indian companies  from journals, websites, research papers and newspapers. The paper describes the current scenario of  the green movement initiatives taken by Indian corporate houses in various industries.
Keywords: Sustainability; Green initiatives; Competitive advantage